Elevated Serum Homocysteine Levels Were Not Correlated with Serum Uric Acid Levels, but with Decreased Renal Function in Gouty Patients - Choi, Sang Tae; Kim, Jin Su; Song, Jung-Soo (Journal of Korean medical science, 2014)
Hyperhomocysteinemia is one of the important factors of the cardiovascular disease, and gout is well known to be associated with cardiovascular disease. There are a few reports on the serum homocysteine (Hcy) levels in patients with gout, however, the results showed discrepancies. In this study, we measured Hcy levels in patients with gout and examined factors associated with the levels of serum Hcy. Ninety-one male patients with gout and 97 age-matched healthy male controls were enrolled in the study. Serum uric acid levels were not significantly different between gout and healthy control groups. However, serum Hcy levels were significantly higher in patients with gout compared to controls (13.96 ± 4.05 µM/L vs 12.67 ± 3.52 µM/L, P=0.035). In gout group, patients with 1-2 stages of chronic kidney disease (CKD) had significantly lower serum Hcy than those with 3-5 stages of CKD (13.15 ± 3.46 µM/L vs 17.45 ± 4.68 µM/L, P<0.001). Multivariate linear analysis revealed an inverse association between serum Hcy and estimated glomerular filtration rate (eGFR) (β=-0.107, P<0.001). In conclusion, serum Hcy was elevated in male patients with gout. Hyperhomocysteinemia was not correlated with serum uric acid, but it was inversely associated with impaired renal function.